Promoting the use of personally relevant stimuli for investigating patients with disorders of consciousness - Perrin, Fabien; Castro, Maïté; Tillmann, Barbara; Luauté, Jacques (Frontiers in Psychology, 2015)
Sensory stimuli are used to evaluate and to restore cognitive functions and consciousness in patients with a disorder of consciousness (DOC) following a severe brain injury. Although sophisticated protocols can help assessing higher order cognitive functions and awareness, one major drawback is their lack of sensitivity. The aim of the present review is to show that stimulus selection is crucial for an accurate evaluation of the state of patients with disorders of consciousness as it determines the levels of processing that the patient can have with stimulation from his/her environment. The probability to observe a behavioral response or a cerebral response is increased when her/his personal history and/or her/his personal preferences are taken into account. We show that personally-relevant stimuli (i.e. with emotional, autobiographical or self-related characteristics) are associated with clearer signs of perception than are irrelevant stimuli in patients with DOC. Among personally-relevant stimuli, music appears to be a promising clinical tool as it boosts perception and cognition in patients with DOC and could also serve as a prognostic tool. We suggest that the effect of music on cerebral processes in patients might reflect the music’s capacity to act both on the external and internal neural networks supporting consciousness.